Cord blood-derived iNK T cells as a platform for allogeneic CAR T cell therapy - Grefe, Maison; Trujillo-Ocampo, Abel; Clinton, Jelita; He, Hong; Yu, Ling; Li, Dan; Ma, Qing; Shpall, Elizabeth J.; Molldrem, Jeffrey J.; Im, Jin S. (Frontiers in Immunology, 2025)
CD1d-restricted invariant Natural Killer (iNK) T cells are a suitable candidate for allogeneic Chimeric Antigen Receptor (CAR) T cell therapy as they do not cause graft-versus-host disease (GvHD) due to the monomorphic nature of CD1d proteins. However, the phenotypic and functional heterogeneity of iNK T cells from adult donors (AD) may lead to the inconstant CAR-iNK T cell products. Cord blood-derived (CB) iNK T cells, in contrast, exhibit inter-donor homogeneity in phenotype including uniform CD4 expression and are enriched in memory iNK T cell populations. Thus, we evaluated the preclinical therapeutic potential of iNK T cells derived from cord blood (CB) as an off the shelf CAR T cell therapy platform, given the dominant presence of CD4+ iNK T cells. First, CB-derived iNK T cells were extremely enriched with CD4+ iNK T cells that express various NK receptors and display iNK-TCR mediated cytotoxicity but in a lesser degree than AD-derived CD4- iNK T cells. When engineered with an 8F4CAR targeting the acute myeloid leukemia-associated antigen PR1 presented in HLA-A2*01, CB-8F4CAR-iNK T cells showed a greater expansion capacity with higher CD62L expression than AD-8F4CAR-iNK T cells but with similar 8F4CAR expression and iNK T purity. CB-8F4CAR-iNK T cells displayed in vitro cytotoxicity against PR1/HLA-A2+ primary Acute Myeloid Leukemia (AML) and cell lines better than AD-8F4CAR iNK T cells and maintained potent cytotoxicity in repeated antigenic challenges. Moreover, CB-8F4CAR-iNK T cells showed anti-leukemia activity in vivo in a dose dependent manner. Lastly, CB-8F4CAR-iNK T cells were polarized to produce Th2-biased cytokines but in a lesser amount after 8F4CAR-mediated leukemia cytolysis compared to iNK-TCR mediated activation. In conclusion, consistent CD4+ phenotype, superior expansion capacity, and enhanced CD62L expression of CB-CAR-iNK T cells suggest that they may provide an alternative off-the-shelf source for effective CAR-iNK T cell therapy, while reducing the risk of severe cytokine release syndrome through their immunomodulatory properties. Thus, our results support the potential use of CB-iNK T cells as an allogeneic CAR-T cell therapy platform as they maintain a potent cytotoxicity with potentially better safety profile given a Th2-biased cytokine production upon activation.